Management of chemical and biological samples for screening applications - Wigglesworth, Mark.; Wood, Terry, Dr.; Wiley InterScience (Online service) (Weinheim : Wiley-VCH, 2012)
"Filling an obvious gap in the scientific literature, this practice-oriented reference is the first to tie together the working knowledge of large screening centers in the pharmaceutical and biotechnological field. It spans the entire field of this emerging discipline, from compound acquisition to collection optimization for specific purposes, to technology and quality control. In so doing, it applies two decades of expertise gathered by several large pharmaceutical companies to current and future challenges in high-throughput screening. With its treatment of libraries of small molecules as well as biobanks containing biomolecules, microorganisms and tissue samples, this reference is universally applicable for any molecular scientist involved in a large screening program."--
Includes bibliographical references and index.
Print version record.
Keywords: Pharmaceutical technology; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Pharmaceutical technology; Electronic books